Study on the behavior of impurity removal from lithium-iron-phosphate slag using the ultrasonic-assisted sulphuric acid leaching - Zhao Y.; Wang Y.-H.; Wu J.-J.; Ma W.-H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The recovery of iron phosphate from the leaching slag of used lithium iron phosphate cathode materials is a crucial step to achieve closed-loop recovery of lithium iron phosphate, which has not yet been effectively accomplished. In the study, ultrasonic-assisted sulfuric acid leaching was used to remove impurities in the iron phosphate, to meet the stringent impurity content requirements for battery-grade iron phosphate regarding impurity content. Optimization of leaching conditions involved a sulfuric acid concentration of 0.2 mol·L-1, acid-leaching time of 30 min, power of 50 W, and reaction temperature of 80℃. Under these conditions, the removal efficiencies of Cr, Cu, Ni, and Zn in iron phosphate were 26.09%, 83.0%, 75.9%, and 96.3%, respectively. Simultaneously, the content of impurity elements Cr and Zn concurred with the standard for battery-grade iron phosphate (HG/T 4701-2021), with both 50 ppm and 10 ppm contents. The leaching results indicated the effectiveness of ultrasound in enhancing the removal of impurity elements in iron phosphate within a sulfuric acid solution. Further analyses, including XRD, particle size, TEM, and XPS indicated that the surface of the iron phosphate particles cavitated after ultrasonic acid leaching, resulting in the formation of numerous pores. Additionally, particle collisions led to a reduction in particle size, with no generation of by-products during the process. This innovative approach not only contributed to the removal of impurity elements but also provided insights into the reuse of leaching slag (iron phosphate) and offered guidance for the recovery of metals from waste lithium iron phosphate cathode materials.